Analysis of the Effect of Gross Regional Domestic Product and Regional Expenditure on Local Own-Source Revenue in Jambi City - Hartoyo, Hartoyo; Putra, Adi; Fahmi, Ali; Nurkodri, Moh Sahroni (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
This study aims to analyze the influence of Gross Regional Domestic Product (GRDP) and Regional Expenditure on Regional Original Revenue (PAD) in Jambi City during the 2015–2024 period. PAD is a crucial indicator in assessing the fiscal independence of a region within the context of regional autonomy. By employing a quantitative approach through multiple linear regression analysis, this research examines both the simultaneous and partial relationships between the independent variables (GRDP and Regional Expenditure) and the dependent variable (PAD). The F-test results show that the regression model is statistically significant at the simultaneous level, with an F value of 15.067 and a significance level of 0.003 (p < 0.05). This indicates that GRDP and Regional Expenditure jointly have a significant effect on PAD. The model also has a coefficient of determination (R²) of 0.811, implying that 81.1% of the variation in PAD can be explained by the two variables. However, the t-test results reveal that only GRDP has a significant partial effect on PAD (p = 0.014), while Regional Expenditure does not show a significant influence (p = 0.632). Conclusion: These findings highlight the importance of regional economic growth in enhancing PAD and underscore the need to evaluate the effectiveness of Regional Expenditure in contributing to local revenue. The policy implication is that local governments should strengthen productive economic sectors that drive GRDP and allocate regional spending to activities with a direct impact on revenue generation. This approach is essential to achieving sustainable regional fiscal independence.